Preventing hospital infections : real-world problems, realistic solutions - Saint, Sanjay; Krein, Sarah L.; Stock, Robert W. ([New York] : Oxford University Press, 2014)
In easy-to-read, user-friendly language,'Preventing Hospital Infections' leads readers through a step-by-step description of a quality improvement intervention as it might unfold in a model hospital, pinpointing the likely obstacles and offering practical strategies for how to surmount them. The text draws on the extensive personal clinical experience of the authors, including examples, anecdotes, and down-to-earth, practical guidance.
Previously issued in print: 2014.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 18, 2016).
Keywords: Infection -- Prevention; Communicable diseases -- Prevention; Hospitals -- Employees -- Health and hygiene